Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1998
DOI: 10.1046/j.1365-2559.1998.t01-2-00410.x
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphous low‐grade adenocarcinoma of minor salivary glands: a study of 17 cases with emphasis on cell differentiation

Abstract: PLGA is a distinctive neoplasm of salivary glands formed by luminal and nonluminal tumour cells with limited patterns of architectural differentiation. The relative proportion of these cells seems to play a significant role in the morphogenesis of these tumours. The overexpression of the bcl-2 protein and the low PI suggest that inhibition of programmed cell death may be involved in the oncogenesis of PLGA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
69
1
4

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 27 publications
8
69
1
4
Order By: Relevance
“…Two of these five cases had a papillary appearance, and Fig. 4a, b of this paper show a tumor with an appearance very similar if not identical to that of CATMSG [15]. It is reasonable to speculate that the tumor pictured in these two figures is likely to be a CATMSG.…”
Section: Differential Diagnosissupporting
confidence: 50%
See 1 more Smart Citation
“…Two of these five cases had a papillary appearance, and Fig. 4a, b of this paper show a tumor with an appearance very similar if not identical to that of CATMSG [15]. It is reasonable to speculate that the tumor pictured in these two figures is likely to be a CATMSG.…”
Section: Differential Diagnosissupporting
confidence: 50%
“…The literature records several possible examples of CATMSG published as PLGA or under other names. Perez-Ordonez et al [15] described 17 PLGAs among which there were two examples of ''PLGA'' of the tongue. In this series, there was a much higher metastatic rate than is usual for PLGA, as 5 of the 17 cases had secondaries in the neck lymph nodes.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…They suggested an epithelial basal/stem/reserve cell origin for polymorphous low-grade adenocarcinoma, but since p63 also stains myoepithelial cells, myoepithelial histogenesis cannot be completely ruled out. Perez-Ordonez et al 17 reported that all polymorphous low-grade adenocarcinoma (100%) expressed 34bE12 in their series. Similarly Gnepp et al and Regezi et al 18,19 reported the expression of high molecular weight keratin in PLGA.…”
Section: Discussionmentioning
confidence: 80%
“…These tumor cells did not express the markers suggestive of myoid/smooth muscle differentiation, consistent with previous reports. 2,11,16,17 However, polymorphous low-grade adenocarcinoma expressed metallothionein, maspin, and p63, the latter two frequently and diffusely. Metallothionein, maspin, and p63 are known to be strongly expressed in simple epithelia, basal/stem cells and myoepithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation